Studi Analisis Keefektifan Pembelajaran E-Learning pada Masa Pandemi Covid-19 di MIN 1 Rembang - Ima Widayanti; Lutfiana; Siti Nafissyatur Riyadhoh; zahro' amalia; Retno Susilowati (JEID: Journal of Educational Integration and Development, 2021)
This article aims to determine the effectiveness of e-learning during the Covid-19 pandemic at MIN 1 Rembang, and to determine the inhibiting and supporting factors in the implementation of learning. The problem in this study is how the environment influences the effectiveness of online learning in the pandemic era for MI / SD students. The research method used is qualitative data method research. The author uses qualitative data collection techniques in the form of interviews with the parties concerned via WhatsApp. Interviews are conversations between two or more people between sources and interviewers to get accurate information from trusted sources. Interviews are conducted by submitting a number of questions from the interviewer to the source. Data analysis was performed using data reduction, display, data verification and conclusion drawing. The results showed that e-learning learning at MIN REMBANG could replace face-to-face learning in schools, but the e-learning process at MIN REMBANG was not as effective as face-to-face learning. Students have difficulty understanding the subject matter and learning. It is necessary to have mature readiness to apply an online learning system. Keywords: , , .